2022
DOI: 10.3389/fendo.2022.829867
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Fat Mass and Fat Distribution With Bone Mineral Density in Non-Obese Postmenopausal Chinese Women Over 60 Years Old

Abstract: BackgroundBone mineral density (BMD) loss is a major complication of menopause, and this loss is closely associated with Fat mass (FM). The relationship between FM, fat distribution (FD), and BMD in postmenopausal women, however, remains incompletely understood. The present study was thus developed to explore these associations between body fat accumulation, FD, and BMD among non-obese postmenopausal women over the age of 60.MethodsThis was a cross-sectional analysis of 357 healthy postmenopausal women between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 38 publications
(38 reference statements)
3
8
0
Order By: Relevance
“…The main nding of this study was that body fat mass (Android or Gynoid) was positively associated with BMD, regardless of gender (Males or Females) and sites (Femur or Lumbar spine). This was similar to the conclusions reached by numerous previous studies, for example, in Asian regions 11,16,20 and European regions 21,22 . Also, some studies have concluded that there was no association or negative association between fat distribution and BMD [23][24][25] .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The main nding of this study was that body fat mass (Android or Gynoid) was positively associated with BMD, regardless of gender (Males or Females) and sites (Femur or Lumbar spine). This was similar to the conclusions reached by numerous previous studies, for example, in Asian regions 11,16,20 and European regions 21,22 . Also, some studies have concluded that there was no association or negative association between fat distribution and BMD [23][24][25] .…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the extant studies that had examined the association between body fat and BMD reached controversial conclusions. In studies of Chinese populations, some studies had concluded that body fat mass was positively associated with BMD in both men and women [11][12][13] , while other studies had concluded that increased fat had a negative effect on BMD 14 . Differential ndings across gender in studies of populations in Brazil 15 , Japan 16 , Australia 17 , and elsewhere were also found.…”
Section: Introductionmentioning
confidence: 99%
“…The positive association was similar to the conclusions reached by numerous previous studies, for example, in Asian regions [ 11 , 16 , 30 ], and European regions [ 31 , 32 ]. Also, some studies have concluded that there was no association or negative association between fat distribution and BMD [ 33 35 ].…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the extant studies that had examined the association between body fat and BMD reached controversial conclusions. In studies of Chinese populations, some studies had concluded that body fat mass was positively associated with BMD in both men and women [ 11 13 ], while other studies had concluded that increased fat had a negative effect on BMD [ 14 ]. Differential findings across gender in studies of populations in Brazil [ 15 ], Japan [ 16 ], Australia [ 17 ], and elsewhere were also found.…”
Section: Introductionmentioning
confidence: 99%
“…These lower oestradiol levels may lead to an imbalance between bone resorption and bone formation (Khosla et al, 2012), as well as affect the mechanosensitivity of osteocytes by reducing the stress response of bone cells (Klein-Nulend et al, 2015). In fact, several studies have shown lower BMD in postmenopausal females compared to premenopausal ones (Fan et al, 2022;Fu et al, 2011). Although theoretically this reduction in oestradiol may promote a loss of BMD, in the literature there is controversy about the effect of OC use on BMD (Rocca et al, 2021).…”
Section: Introductionmentioning
confidence: 99%